2009
DOI: 10.1007/s12035-009-8065-0
|View full text |Cite
|
Sign up to set email alerts
|

Polarity Regulation in Migrating Neurons in the Cortex

Abstract: The formation of the cerebral cortex requires migration of billions of cells from their birth position to their final destination. A motile cell must have internal polarity in order to move in a specified direction. Locomotory polarity requires the coordinated polymerization of cytoskeletal elements such as microtubules and actin combined with regulated activities of the associated molecular motors. This review is focused on migrating neurons in the developing cerebral cortex, which need to attain internal pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 200 publications
(210 reference statements)
2
31
0
Order By: Relevance
“…Axon specification seems to occur during the transition from multipolar to bipolar morphologies in the IZ. We believe that this transition reflects neuronal polarization in vivo, which has been described previously (22,23,58,60,62).…”
Section: In Vivo Role Of Trks and Camkksupporting
confidence: 76%
See 2 more Smart Citations
“…Axon specification seems to occur during the transition from multipolar to bipolar morphologies in the IZ. We believe that this transition reflects neuronal polarization in vivo, which has been described previously (22,23,58,60,62).…”
Section: In Vivo Role Of Trks and Camkksupporting
confidence: 76%
“…These multipolar neurons subsequently transform to exhibit a bipolar morphology with a leading and a trailing process (bipolar neurons) and migrate along the radial fibers of the progenitor cells toward the cortical plate (CP) (6,58,60,61). Cultured cortical neurons specify axons in a manner similar to that observed in hippocampal pyramidal neurons (6,62). RT-PCR analysis revealed that CaMKK was expressed in multipolar neurons ( fig.…”
Section: In Vivo Role Of Trks and Camkkmentioning
confidence: 85%
See 1 more Smart Citation
“…In vivo the situation is more complex because bipolar neurons typically migrate and it is difficult to distinguish polarity events needed to support directed migration, including changes in MT and actin dynamics (Reiner and Sapir, 2009), from those specifying axon-dendritic polarity.…”
Section: Intracellular Dynamics In Bipolar Neurons In Situmentioning
confidence: 99%
“…35 This not only applies to neural progenitors where, e.g., the apical-basal polarity is key for sustaining interkinetic nuclear migration and thus maintaining the neural progenitor pool during neocortical development, 36, 37 but also to postmitotic cells such as neurons. 38 Given the current model that CDK5RAP2 mutations cause microcephaly not only via the temporarily increased differentiation of stem cells, but also through a premature shift from symmetric to asymmetric cell divisions and thus premature neurogenesis, we applied a protocol that enables spontaneous mESC differentiation after withdrawal of mLIF. We hereby investigated whether Cdk5rap2-depleted mESC generally tend to differentiate prematurely or if this is specific for neural differentiation.…”
Section: Discussionmentioning
confidence: 99%